Aplikasi Metode Multycriteria Decision Making (MCDM)dengan Teknik Pembobotan Dalam Mengidentifikasi dan Mendesain Kawasan Konservasi Perairan Daerah di Kabupaten Luwu Utara, Provinsi Sulawesi Selatan - Chair Rani; M. Natsir Nessa; Ahmad Faizal; M. Farid Samawi (Hasanuddin University, 2014)
The study, in 2012, has successfully formulated with the MCDM for each allocation of space in KKPD allotment (core areas, sustainable fisheries zone, used zone, and other zones). This weighting techniques need to be tested and be implemented in identifying and designing the KKPD in the study area. This study aims to identify and map the biophysical conditions and the potential of coastal and marine natural resources in marine conservation area candidate, North Luwu Regency; to identify the areas suitable for the KKPD based on weighting technique with the MCDM method; and to evaluate potential candidates for marine protected areas in the coastal region. This study used a survey method to perform in situ measurements of physico-chemical parameters, conducted a survey of coastal ecosystems using the transect method. The socio-economic data of coastal communities were collected using the questionnaire. The biophysical conditions and marine resources were analyzed using descriptive statistical methods. The results showed that the candidate region has a rich diversity of coastal ecosystems, but the ecosystem, particularly seagrass beds and coral reefs have been in damaged category. Only the mangrove ecosystem that was still in a good condition category with moderate-to-heavy levels of density. There were 6 species of seagrasses and 6 species of mangroves and 71 species of reef fish. It was discovered 2 regions corresponding to the allotment of the Core Zone, which is in the Region I and III with the total area of 654.22 hectares. For sustainable fisheries zone, Region II and IV would be the first choice with the total area of 620.27 hectares. The Used Zone was identified in the Region V with total area of 480.66 hectares. The total area of the region was equal to 1755.15 hectares. Marine protected areas of was suggested to the protection of coastal ecosystems including mangroves, seagrass beds, and coral reefs and its associated biota, especially the protection of local feeding ground of several species (sea turtles and dugongs).